The Language of Trauma: A Linguistic Analysis of Interviews with Holocaust Survivors - Altman, Emilie (My University, 2023)
We performed quantitative analysis on transcriptions of 784 interviews with Holocaust survivors. The interviews were collected by the University of Southern California Shoah Foundation, and the first 15 minutes of each interview had been transcribed using automatic speech recognition. The survivors were an aging population as the interviews were conducted around fifty years after the end of the Holocaust. We used statistical methods and algorithms to analyze the data including keyness analysis, topic modeling, and emotionality analysis. We used the Contemporary Corpus of American English (COCA) as a comparative corpus for these analyses. Overall, we found that survivors prioritized themes of the Holocaust and their families in the interviews. Specific words and themes reoccurred across the corpus demonstrating a collective and consistent memory of trauma. Our emotionality analyses revealed that survivors used slightly more positive language and fewer words relating to anger, disgust, and fear than the speakers in our comparative corpus.
Keywords: Trauma; Holocaust; Linguistics; Corpus Analysis